The Physiological Changes In The Postpartum Period After Childbirth - Christian Martin; Muhammad viky; Rokibullah Rokibullah; Haleyoan Sofinia (Pelopor Publikasi Akademika, 2022)
The physiological changes that occur during the puerperium are very clear, where the process of pregnancy goes in reverse. Physiological changes that occur during pregnancy will return to normal during the postpartum period. Pregnancy and childbirth are physical events, so the concept is that during the puerperium the body will recover. This study aims to provide an explanation of the physiological changes during the puerperium after childbirth and to add insight in describing precisely and training the scientific thinking needed to be able to analyze a problem accurately and quickly. This study used the contrast review method, meaning the journal review method by finding differences between several research journals and then drawing conclusions. The results of this study found that there were several physiological changes during the postpartum period including changes in the reproductive system, changes in the endocrine system, changes in vital signs, changes in the cardiovascular system, changes in the blood circulation system, changes in the hematological system, and changes in the respiratory system.